Wild flowers - Fiedel, Roslyn (Boston, Massachusetts : Houghton Mifflin Company, 1971)
The atom of expression in Wild Flowers is within every youngster. I gathered my students, we danced and "became" the flowers, the withes, and the wind.
Keywords: PICTURES